2017
DOI: 10.1097/01.nep.0000000000000176
|View full text |Cite
|
Sign up to set email alerts
|

Exploring APN Students’ Perceptions, Self-Confidence, and Satisfaction With Clinical Simulation

Abstract: The purpose of this study was to explore advanced practice students' perceptions, self-confidence, and satisfaction with clinical simulation as a learning tool. The simulation was part of a health assessment course with 69 students, 25 of whom had no RN experience. On average, students were undecided but trended toward agreement that each key simulation feature was present in the simulation. Students without experience were significantly less likely to feel supported during the simulation and to endorse the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 4 publications
1
4
0
1
Order By: Relevance
“…Also, a significant difference was detected between students with different work experience times ( p = 0.007) (Table 4 ). These results are similar to a previous American study [ 15 ]. In the current study, the simulation was designed based on the clinical nursing process and basic nursing skills ranging in difficulty from simple to complex.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Also, a significant difference was detected between students with different work experience times ( p = 0.007) (Table 4 ). These results are similar to a previous American study [ 15 ]. In the current study, the simulation was designed based on the clinical nursing process and basic nursing skills ranging in difficulty from simple to complex.…”
Section: Discussionsupporting
confidence: 93%
“…Compared with students with less work experience, those with more experience showed significantly higher self-confidence in the simulation ( p = 0.002). Previously, APN students who had work experience had higher self-confidence scores than those without, but the difference was not significant [ 15 ]. It is not surprising that students with more work experience feel more confident.…”
Section: Discussionmentioning
confidence: 99%
“…A study of undergraduates showed improvements in pre-clinical skills, facilitation of the learning process, and improved communication skills [ 11 ] but could not confirm knowledge transition to the clinical field. Given the lack of instructors, restrictions on patient access in clinical practice, and decreases in clinical field exposure [ 26 , 27 ], high-quality simulation education is critical to APN education. Education on case studies and objective structured clinical examination (OSCE) was reported by GNPs to be difficult to translate into actual performance [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…14,15 La satisfacción de los alumnos en el uso de la simulación clínica también es relatada en otras investigaciones. 16,17 Se trata de un elemento importante en la evaluación de la efectividad de una estrategia de enseñanza, pues indica mayor involucro y motivación del estudiante para el aprendizaje. 18 Incluso están disponibles algunos instrumentos validados para su uso en la simulación, que buscan evaluar la satisfacción del estudiante, como la Escala de Satisfacción con las Experiencias Clínicas Simuladas-ESECS 18 validada al portugués y la Simulation Experience Scale-SSES, 19 entre otras existentes en lengua inglesa.…”
Section: Discussionunclassified